Direct and indirect effects of solar ultraviolet-B radiation on long-term decomposition - Pancotto, Veronica Andrea (2005)
As a result of stratospheric ozone depletion, more solar ultraviolet-B radiation (UV-B, 280-315 nm) is reaching the Earth's surface. Enhanced levels of UV-B may, in turn, alter ecosystem processes such as decomposition. Solar UV-B radiation could affect decomposition both indirectly, by changes in the chemical composition of leaves during growth, or directly by photochemical breakdown of litter and through changes in decomposer communities exposed to sunlight. In this experiment, we studied indirect and direct effects of solar UV-B radiation on decomposition of barley (Hordeum vulgare). We used barley straw and leaf litter grown under reduced UV-B (20% of ambient UV-B) or under near-ambient UV-B (90% of ambient UV-B) in Buenos Aires, Argentina, and decomposed the litter under reduced or near-ambient solar UV-B for 29 months in Tierra del Fuego, Argentina. We found that the UV-B treatment applied during growth decreased the decay rate. On the other hand, there was a marginally significant direct effect of elevated UV-B during the early stages of decomposition, suggesting increased mass loss. The effect of UV-B during growth on decomposition was likely the result of changes in plant litter chemical composition. Near-ambient UV-B received during plant growth decreased the concentrations of nitrogen, soluble carbohydrates, and N/P ratio, and increased the concentrations of phosphorus, cellulose, UV-B-absorbing compounds, and lignin/N ratio. Thus, solar UV-B radiation affects the decomposition of barley litter directly and indirectly, and indirect effects are persistent for the whole decomposition period.